(untitled) (Bulletin KNOB, 2015)
During the Dutch Golden Age, Amsterdam grew from a modest little town on the river Amstel into a powerful trading metropolis. Thanks to several very large-scale expansion schemes (in particular the third and fourth expansions), it became one of the biggest cities in Europe. This article does not focus on the design or implementation of the urban expansions. Instead, it concentrates on a subsequent phase in the development: the moment when the large public project broke up into thousands of private projects, which occurred when the government sold off building plots. The key questions posed in this article are whether the large scale of these expansions stimulated entrepreneurship in the building sector, and how that affected the urban landscape. Was there any increase in scale in the building sector, how did the sector deal with the opportunities offered by urban expansion and what strategies did it employ? It is the first time that such a very large quantitative study has been carried out for an early modern city. Amsterdam possesses exceptional series of sources that we were able to combine for this purpose. During the urban expansions, thousands of plots of land were sold at a succession of auctions, which resulted in maps and auction ledgers. These provide information about the plots and their buyers and allow us to calculate the proportion of building sector craftsmen investors and to work out which market segments they focused on (based on the location, size and price of the plots). Because we are primarily interested in the impact of major building booms, we concentrate on the periods 1614–1617. (when the land in the third expansion was sold and built on) and 1660–1699 (ditto for the fourth expansion). It transpires that building sector craftsmen were heavily over-represented in the real estate market compared with their colleagues from other production sectors. Nevertheless, only five to ten per cent of building sector cra’smen invested in land, which they usually bought in a dispersed fashion. In this way they gained access to the market, where they invested mainly in land intended for the social middle classes. (This was in contrast to the large-scale investors, who tended to concentrate on the market for workers’ housing.) In a few instances they built a house for themselves with a workshop from where they could offer their services to clients in the neighbourhood. In other cases, in particular among bricklayers, it seems that in buying land they were trying to gain direct access to the new-build market. This group sold their land fairly quickly, and in the case of a few master bricklayers we were able to ascertain that they immediately started building for the new owner. Quite a number of building cra’smen who started building on their own initiative, sold the building under construction at an early stage to the future owner. This strategy indicates that they had insufficient capital to pre-finance the entire construction and to market a finished product. In contrast to Niels Prak’s findings with regard to nineteenth-century Amsterdam, master building cra’smen did not immediately, and certainly not in large numbers, seize the opportunities offered by the large-scale urban expansions in seventeenth-century Amsterdam, at least not by building for the market on land they owned. Further research will be needed to show to what extent they opted for other forms of enterprise, such as a combination of builders’ merchant and construction work, or coordination of the building process for subcontractors. During the third expansion fairly large parcels of land were released, many of which were a’erwards subdivided, sometimes in order to build rows of smaller, uniform dwellings. The fourth expansion, by contrast, supplied a diversified parcellation that was much better aligned with market demands: large mansions on Herengracht and Keizersgracht, shop-dwellings along the radial streets, and a more mixed milieu with middle-class and smaller dwellings and industrial premises in the areas closer to the urban periphery. The urban structure laid down in those seventeenthcentury urban expansions and the buildings constructed on the allocated land, continue to determine the Amsterdam cityscape up to the present day.